Weak coordination between leaf drought tolerance and proxy traits in herbaceous plants - Májeková, Maria; Hájek, Tomáš; Albert, Ágnes J.; Bello, Francesco; Doležal, Jiří; Götzenberger, Lars; Janeček, Štěpán; Lepš, Jan; Liancourt, Pierre; Mudrák, Ondřej (Functional ecology, 2021)
Increased drought is predicted to have a major impact on plant performance under environmental change. Yet leaf hydraulic traits directly related to drought tolerance, such as leaf turgor loss point (πtlp), are under‐represented in trait‐based studies and have been largely overlooked within the main frameworks evaluating trait–trait coordination and trade‐offs—the leaf economics spectrum (LES) and the global spectrum of plant form and function. Using 122 herbaceous species from the Central European temperate grasslands, we investigated (a) the coordination between πtlp and traits often used as proxies for drought tolerance, namely SLA, leaf area (LA), leaf dry matter content (LDMC), leaf thickness (LT), plant height and intrinsic water use efficiency (iWUE); (b) whether the strength of the trait–trait relationships differed across plant functional types (PFTs: graminoids and forbs) and depended on species phylogeny; and (c) whether single or multiple traits, combined with either PFTs or phylogenetic relatedness, provide a good prediction of πtlp. A more negative πtlp (higher leaf drought tolerance) was coordinated with higher LDMC and higher iWUE. This pattern was consistent among PFTs and also after accounting for phylogenetic relatedness. However, the coordination of πtlp with other traits was weak. For LT and height, it was driven by the differences between PFTs. For SLA and LA, it was only observed after accounting for phylogenetic relatedness. The most parsimonious model predicting πtlp as a function of other traits retained LDMC and LA (adj. R2 = 0.37). Since πtlp showed a strong phylogenetic signal, accounting for the influence of phylogenetic relatedness further improved πtlp prediction by 17%. In herbaceous temperate plants, there is relatively weak coordination between leaf drought tolerance (πtlp) and traits representing key dimensions of the LES and the global spectrum of plant form and function. None of the proxy traits considered here, alone or in combination, provided a strong prediction of πtlp across a large number of grassland plant species. Therefore, our work emphasizes the need for direct measurements of leaf hydraulics when estimating plant drought responses to better understand and predict species responses to environmental change. A free Plain Language Summary can be found within the Supporting Information of this article. A free Plain Language Summary can be found within the Supporting Information of this article.